Pengaturan Perjanjian Asuransi Jiwa Unitlink dalam Kaitannya dengan Perlindungan Hukum Pemegang Polis - Harvia Santri, Selvi; Fauzi, Wetria (Universitas Ekasakti, 2023)
Insurance is a financial service product that offers risk protection against losses. Risks can vary, such as the risk of death, risk of disability, and risk of asset damage. Insurance that is currently in great demand is unit-link life insurance, which not only provides protection for life but also investment. In Unitlink Insurance, part of the money deposited in premiums will be used for the customer's investment needs. However, in practice, unitlink life insurance products cause many problems, namely failure to pay unitlink life insurance companies in disbursing claims to policyholders, therefore policyholders need legal protection to obtain their rights, clear and firm legal regulations are needed that regulate legal protection the policy holder. The aim of this research is to determine the regulation of unitlink life insurance and to determine the form of legal protection for unitlink life insurance policy holders. The type of research used is normative juridical. The results of this research show that unitlink life insurance regulations are contained in several provisions, namely Law No. 40 of 2014 and POJK provisions. Legal protection for policy holders is regulated in article 53 of Law No. 40 of 2014 concerning Insurance Business which states that legal protection for policy holders is carried out by means of the insurance company being obliged to register insurance with the policy guarantee institution. The form of legal protection for policy holders is also regulated in Law No. 8 of 1999 concerning Consumer Protection regarding the Rights and Obligations of Business Actors, in this case Insurance Companies.